Studi Korelasional Prestasi Belajar Siswa dengan Kemampuan Menulis Narasi pada Anak Sekolah Dasar - Farih Indi Rifatin; Arif Siswanto (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Correlational Study of Student Learning Achievement and Narrative Writing Skills in Elementary School Children Background: Student learning achievement can be known by conducting an assessment process through evaluation activities so that the evaluation results can describe student achievement by looking at their abilities. The ability to write narratives is one of the skills that must be mastered well by students because through writing narratives, students can express their ideas, feelings, and desires. Objective: This study aims to determine the relationship between student learning achievement and narrative writing skills grade 4 elementary school students in Brebes. Method: This research is a type of quantitative research using a correlational research design. The sampling technique in this study used total sampling technique. The collected data were analyzed univariately and bivariately. The statistical test used is the Contingency Coefficient test. Results: Based on the results of data analysis using the Contingency Coefficient test, a significance value of 0.001 was obtained, so it can be stated that there is a significant and positive relationship between student learning achievement and the ability to write narratives in grade 4 elementary school students in Brebes. The value of the correlation coefficient is 0.427 which shows the magnitude of the strength of the relationship between the two variables in the medium category. Conclusion: There is a relationship between learning achievement and narrative writing skills in grade 4 elementary school students in Brebes. Keywords: learning achievement, narrative writing, elementary school